Police stop and search in Spain: an overview of its use, impacts and challenges. - Arenas-García, Lorea; García-España, Elisa (Universitat Pompeu Fabra, 2022)
Even though in Spain there are no complete, public and updated national statistics on police stops with information on ethnicity, data provided by some local police forces and academic research prove that the police disproportionately stop and search minority groups. This practice affects the sense of belonging of individuals (who experience shame and humiliation), leads to institutional discrimination, and reduces the legitimacy and trust in law enforcement. This paper aims to analyze the Spanish empirical evidence about police stops practices and its effects on citizens conducting a systematic review on existing literature. The main results show that: police stops are carried out based on racial profiling; consequences of police discrimination had a more negative impact on individuals who had been or perceived to have been stopped due to racial reasons; it is necessary to develop more qualitative studies that complement the quantitative methodologies in order to gather richer information about experiences on police treatment, particularly at stops.
Política de acceso abierto tomada de: https://indret.com/criterios-de-publicacion/
Keywords: Discriminación racial - España; Policía - Actitudes; Police stop and search; Racial profiling; Discrimination; Minority groups